Vine vigour modulates bunch microclimate and affects the composition of grape and wine flavonoids: an unmanned aerial vehicle approach in a Sangiovese vineyard in Tuscany. (5th July 2017) - Romboli, Y.; Di Gennaro, S.F.; Mangani, S.; Buscioni, G.; Matese, A.; Genesio, L.; Vincenzini, M.
Abstract: Background and Aims: This study focused on the impact of vine vigour on Sangiovese grapes and wines, applying a high‐resolution remote sensing technique by an unmanned aerial vehicle (UAV) platform to identify vigour at the single vine level within a vineyard. Methods and Results: A factorial field experiment was established combining two vigour classes (low and high) and two bunch positions within the canopy (north‐facing and south‐facing). The remote sensing technique by the UAV platform identified the heterogeneity in terms of vigour within the vineyard. Vine vigour influenced significantly the composition of anthocyanins, flavonols and flavan‐3‐ol monomers of the grapes and wines. Conclusions: The work confirmed that UAV‐based remote sensing enabled the successful evaluation of vine vigour at high resolution and that vigour influences the flavonoid monomeric compounds as a function of bunch position within the canopy. Significance of the Study: Understanding the impact of spatial variability in a vineyard on grape composition should assist the viticulturist and winemaker toward the adoption of adequate viticultural management operations capable of adding value to their wines.